Electrodermal Activity Analysis for Training of Military Tactics. (September 2016) - Boyce, Michael W.; Goldberg, Benjamin; Moss, Jason D.
This study examined the differences in the electrodermal activity (EDA) of 19 ROTC cadets viewing a 2D or 3D perspective display. Skin conductance responses (SCRs) were analyzed using a multistep visual analytic process and coded according to participant and condition. Results show non-significant differences SCRs between conditions, however since it is only an initial study, more research needs to be done before definitive conclusions can be made. Future investigations involving mixed method research design are discussed with a specific emphasis on user engagement and workload. The results of this initial study will be incorporated into future research with the United States Military Academy at West Point.